The development of teachers' pedagogical content knowledge (PCK) in the mediation of chemical equilibrium: A formative interventionist study - Manamike, Tasara (Rhodes University, Faculty of Education, Department of Education)
Persistent student errors in understanding chemical equilibrium as shown by poor student achievement in national examinations reflect student difficulties in learning and deficiencies in teaching methodologies. Studies which have been conducted in Namibia have explored the teaching of chemical equilibrium and revealed that teachers seem not to have adequate pedagogical content knowledge (PCK) for mediating chemical equilibrium and therefore there is a need for continuing professional development (CPD). However, it seems the CPD facilitators also find this topic difficult and are unsure of which methods are really effective owing to the disagreements among teachers and researchers. In addition, current CPD practices ostensibly fail to address the teachers' needs because the facilitators have their own commitments and accountabilities and may ignore teachers' contexts. It is against this backdrop that I conducted this formative interventionist study to improve teachers' PCK for mediating chemical equilibrium through expansive learning (learning something that does not yet exist). A blend of the interpretivist and critical paradigm underpinned this study, which assumed a transactional epistemology. The qualitative case study research design was used to gather in-depth information about the multiple realities of the participants, bearing in mind that teaching is idiosyncratic, and the teaching approaches or strategies employed heavily depend on the contexts. Accordingly, the cultural historical activity theory was used to guide the teachers' activities during the intervention for generating the data which were analysed using the topic-specific pedagogical content knowledge. The study revealed that the participants faced challenges in their teaching, namely: (i) students' difficulties with comprehension and (ii) teachers' instructional problems or deficiencies in instructional skills. The findings also revealed that the intervention enabled the participants to collectively transform their practices and therefore address the major challenges in their practices, that is, they expansively learnt how to effectively teach chemical equilibrium.
Keywords: Chemical equilibrium; Chemistry-- Study and teaching (Secondary) Nambia; Expansive learning; Career development Nambia; Professional learning communities Nambia; Pedagogical content knowledge; Cultural-historical activity theory